2007
DOI: 10.1007/s12094-007-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for radiation-induced pulmonary toxicity after three-dimensional conformal chemoradiation in locally advanced non-small-cell lung cancer

Abstract: COPD and NTCP are predictive of severe RP. Careful medical evaluation and meticulous treatment planning are of paramount importance to decrease the incidence of severe RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Including these parameters (MLD, V 5 , V 13 , V 20 , and V 40 ) in a multivariate logistic regression analysis revealed that only the MLD was significantly associated with RP (data not shown). However, these data should be interpreted with caution since it is known from studies with conventional fractionated RT evaluating clinical and dose factors predicting RP that there is a large heterogeneity of results (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), whereby no validation was performed. One collaborative study from Duke University and The Netherlands Cancer Institute developed a prospective method to predict RP from dose and clinical parameters in one group of patients, but validation failed in another group of patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Including these parameters (MLD, V 5 , V 13 , V 20 , and V 40 ) in a multivariate logistic regression analysis revealed that only the MLD was significantly associated with RP (data not shown). However, these data should be interpreted with caution since it is known from studies with conventional fractionated RT evaluating clinical and dose factors predicting RP that there is a large heterogeneity of results (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), whereby no validation was performed. One collaborative study from Duke University and The Netherlands Cancer Institute developed a prospective method to predict RP from dose and clinical parameters in one group of patients, but validation failed in another group of patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Videtic et al found low DLCO (<60% predicted) to be significantly associated with more treatment breaks and worse survival in a study of patients treated with radiation therapy for small-cell lung cancer [21] . Other studies have also identified Karnofsky performance status, FEV1, and a diagnosis of COPD as significant factors in predicting RILI risk and other treatment-related complications [8,22] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of predictive models have been posited to ascertain which patients are likely to develop RILI given similar radiation doses and treatment parameters [2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…In adults and children, predisposing factors may effect the risk of pneumonitis and fibrosis (e.g. smoking and related chronic emphysema, pneumonia, asthma) (1,2,3). These predisposing factors and the context of RT (e.g.…”
Section: Specific Examples Of Late Effectsmentioning
confidence: 99%
“…In non-smokers age > 59 years receiving RT for breast cancer, the risk of RP was elevated (15). Active smoking has been implicated by others to provide a slight protective benefit, possibly related to immune suppression (1). In 606 patients with breast and esophageal carcinoma, the incidence of RP for smokers compared to non-smokers was 0.4% vs. 3.6% (p=0.022) (16).…”
Section: Specific Examples Of Late Effectsmentioning
confidence: 99%